SOSIALISASI PROGRAM BANTUAN STIMULAN PERUMAHAN SWADAYA (BSPS) BAGI MASYARAKAT BERPENGHASILAN RENDAH - Yemima Erika Netta; Evinalia Yeba (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
The Self-Help Housing Stimulant Assistance Program (BSPS) is a government initiative aimed at improving the quality of housing for low-income communities through community empowerment and self-help approaches. However, many community members still have limited understanding of the objectives, requirements, and implementation mechanisms of the program. This community service activity aimed to enhance public understanding of the BSPS program through socialization activities involving low-income communities, village officials, and community leaders. The activity employed an educational and participatory approach through presentations, interactive discussions, and question-and-answer sessions. The results showed that the socialization activity improved participants’ understanding of the program objectives, beneficiary requirements, implementation procedures, and the rights and responsibilities of beneficiaries. Furthermore, the activity encouraged community participation in supporting program implementation and increased awareness of the importance of adequate housing for family welfare. The success of the activity was supported by participants’ enthusiasm, interactive communication, and collaboration between the implementation team and village authorities. Therefore, the socialization of the BSPS program can be considered an effective effort to improve community understanding and readiness to participate in government housing assistance programs.